French colonial Dakar : The morphogenesis of an African regional capital (Book collections on Project MUSE., 2016)
This book deals with the planning and architectural cultures that shaped the model space of French colonial Dakar, a prominent city in West Africa. With a focus on the period from the establishment of the city in the mid-nineteenth century until the interwar years, the book reveals a variety of urban politics, policies and practices, and complex negotiations on both the physical and conceptual levels. The study of the extra-European planning history of Europe has been a burgeoning field in scholarly literature. By exploring colonial urban space in sub-Saharan Africa, a relatively untreated reg.